Case Report: Avelumab and ruxolitinib to manage polycythemia vera and secondary metastatic Merkel cell carcinoma: a possible successful combination - Masucci, Chiara; Passucci, Mauro; Scalzulli, Emilia; Carmosino, Ida; Capriata, Marcello; Costa, Alessandro; Ielo, Claudia; Martelli, Maurizio; Breccia, Massimo (Frontiers in Oncology, 2023)
We describe a case of second primary malignancy in a 65-year-old patient affected by polycythemia vera treated with the JAK 1/2 inhibitor ruxolitinib. The latter is recognized as a risk factor for the onset of non-melanoma skin cancers in many retrospective and perspective studies, but the concomitant use of ruxolitinib with new immunotherapies is very rarely reported and the safety of this association is still not clear. In our case, ruxolitinib combined with the anti-PD-L1 avelumab demonstrated both safety and efficacy for the hematologic disease control and the underlying carcinoma remission.